An Empirical Assessment of Economic and Political Challenges of European Union Accession - Tamazian, Artur (2012)
The collapse of the Soviet Union was an exceptional experiment in the economic history of the world, which made the post-socialist countries the subject of various economic studies. Different researchers and organizations tend to monitor the progress of economic and institutional reforms through inventing different indexes (indicators), apparently trying to understand how to detect the end of the transition process. The European Union, opening its door to accession candidates and starting negotiations with a number of eastern European and Baltic states, was the first to rely on those assessments of progress in reforms for making decisions on the readiness of the countries in terms of economic and institutional development to become a member of the European family. This study tries to link the actual assessments of reforms (start of negotiations) and the available set of indicators to construct an empirical model. We apply statistical techniques of limited dependent variable models to reveal the most important criteria followed by the 'EU admission committee' and capture them in limited dependent variable models, which are applied to evaluate the readiness of a number of other post-socialist countries to start hypothetical negotiations with the EU. Based on available empirical results the factors captured in the model include the share of public expenditure in GDP, GDP per capita, private sector share of GDP, share of trade with EU in external turnover, democratization and inflation (macroeconomic stability). Our empirical assessments show that there are several transition economies (Albania, Armenia, and Georgia), which despite not having candidate status, offer better general standing in terms of 'accession criteria' than the current candidates. This fact may suggest to policy-makers (other geopolitical conditions being equal) to consider these countries for future EU enlargement waves.